ANALYZING THE INTEGRATION OF MEDICAL STAFF MENTAL HEALTH SERVICES INTO PEDIATRIC CARE: A SYSTEMATIC REVIEW (Lex localis - Journal of Local Self-Government, 2024)
Background: Pediatric mental health disorders are prevalent and under-treated, with integration of behavioral health into pediatric care emerging as a promising strategy to improve access and outcomes. This review synthesizes empirical evidence on integration models led by medical staff within pediatric care settings.Methods: Following PRISMA 2020 guidelines, a systematic search of PubMed, PsycINFO, Scopus, Web of Science, and Embase was conducted for studies published between January 2010 and January 2025. Eligible studies examined integration of mental health services into pediatric care for populations aged 0–18 years, reporting outcomes related to utilization, access, clinical improvement, or cost-effectiveness.Results: Twenty-four studies met inclusion criteria, including randomized controlled trials, cohort studies, cross-sectional analyses, and implementation studies. Integration models included co-location, collaborative care, universal screening, stepped care, and health coaching. Key findings indicated improved service utilization, reduced wait times, higher rates of same-day access, and in some cases, better symptom management. Subgroup analyses revealed differential benefits by age, sex, and insurance status. Cost evaluations suggested integration is financially sustainable when coupled with efficient workflow and policy support.Conclusions: Integration of medical staff mental health services into pediatric care improves access, engagement, and certain clinical outcomes. Success depends on tailored implementation, interprofessional collaboration, policy alignment, and equitable design. Further research should address long-term effectiveness and context-specific adaptations.